Bemerkungen zum Martyrologium Syriacum - Schäferdiek, Knut (Analecta Bollandiana, 2005)
The Martyrologium Syriacum keeps strictly to the original pattern of a martyrology. As a rule it only lists martyrs, including a series of bishops of Antioch erroneously considered martyrs. Exceptions are three commemorations of bishops, which differ from the usual entries by their form. The idea of an universal martyrology was suggested by one of the sources which was used by the compiler but was not identical with the lost "compilation of ancient martyrs" of Eusebius of Caesarea. Unfounded is the assumption of an "Arian" tendency as well as the supposition that the first entries were intended to form a liturgical Christmas cycle.